Cerium modified polysiloxane fluid with high heat conductivity coefficient and preparation method thereof

By introducing cerium elements into the polysiloxane fluid to form Si-O-Ce bonds, the problem of insufficient thermal conductivity of silicone polymer materials is solved, and the thermal conductivity of thermal interface materials is significantly improved.

CN119591877APending Publication Date: 2025-03-11HANGZHOU NORMAL UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411520825.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The thermal conductivity of existing silicone polymer materials is insufficient, which limits the thermal conductivity of silicon-based thermal interface materials.

Method used

By reacting the cerium organometallic compound with polysiloxane under a closed inert gas environment, Si-O-Ce bond is formed, and the thermal conductivity of the polysiloxane fluid is increased.

Benefits of technology

The thermal conductivity of the polysiloxane fluid is significantly improved, and the thermal conductivity of the thermal interface material is significantly improved by application in thermal interface materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119591877A_ABST
    Figure CN119591877A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of high polymer materials, and discloses a cerium modified polysiloxane fluid with a high heat conductivity coefficient and a preparation method thereof, and the preparation method comprises the following steps: carrying out a reaction on a cerium organic metal compound and polysiloxane in a closed inert gas environment, filtering the product, and carrying out reduced pressure distillation to remove low-boiling-point substances to obtain a cerium modified polysiloxane material. The generated Si-O-Ce bonds are used for improving the heat conduction performance of the polysiloxane fluid, and the heat conduction coefficient of the polysiloxane fluid is increased; when the cerium-modified polysiloxane fluid is used for replacing unmodified polysiloxane fluid to be applied to the thermal interface material, the heat conductivity coefficient and the penetration of the thermal interface material are both improved. The preparation method is simple in process and easy to industrialize.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to a cerium-modified polysiloxane fluid with high thermal conductivity and a preparation method thereof. Background Art

[0002] Linear or low-branched silicone polymer materials are in the form of liquid oil at room temperature. Since Si-O-Si bonds have high bond energy and are arranged in a spiral shape in space, Si-O-Si bonds have good weather resistance, high and low temperature resistance and good air permeability, and are widely used as the base material of various thermal interface materials such as thermal conductive silicone paste, thermal conductive silicone grease, thermal conductive silicone rubber, and thermal conductive silicone gel. Compared with commonly used metal oxides or metal powder thermal conductive fillers such as aluminum oxide, zinc oxide, aluminum nitride, boron nitride, aluminum powder, and silver powder, silicone materials are poor conductors of heat, and their thermal conductivity is only 0.179W / (mK).

[0003] Silicon-based thermal interface materials such as thermal conductive silicone paste, thermal conductive silicone grease, thermal conductive silicone rubber, and thermal conductive silicone gel usually use metal oxides or metal powders with high thermal conductivity such as aluminum oxide, zinc oxide, aluminum nitride, boron nitride, aluminum powder, and silver powder as thermal conductive fillers, and use non-cross-linked linear or low-branched polysiloxanes, and fully cross-linked or partially cross-linked polysiloxane network structures as the base material of the silicon-based thermal interface materials, and are obtained by mixing, dispersing, or cross-linking and curing.

[0004] Although the amount of silicone material used in the thermal interface material system usually does not exceed 10wt% or even lower, the thermal conductivity of polysiloxane has become a key factor restricting the thermal conductivity of thermal interface materials. According to the theoretical calculation formula of the thermal conductivity of composite materials, it can be inferred that the thermal conductivity of composite materials presents a "barrel effect", that is, the thermal conductivity of the composite material system depends to a large extent on the component with the smallest thermal conductivity in the system. Starting from the component with the smallest thermal conductivity in the composite material system, if the thermal conductivity of this component can be improved by physical or chemical means, the thermal conductivity of the composite material will show a large change. Nowadays, it is difficult to make major breakthroughs in the research and development of low-cost, high thermal conductivity fillers. Therefore, how to improve the thermal conductivity of polysiloxane materials, that is, to research and develop the so-called intrinsic thermal conductive polymers, has become the focus of academic and industrial attention.

[0005] Pan Hongmei et al. (Coating Industry, 2024, 54(6): 82-88) summarized the research progress of intrinsic thermal conductive insulating liquid crystal epoxy resins, pointing out that by designing and changing the structure of epoxy resin molecules and chain segments, special physical structures (such as orientation structure, liquid crystal structure and crystal structure, etc.) can be obtained, thereby improving the orderliness of the internal structure of the resin and improving the thermal conductivity of the epoxy resin. For example, the orderliness of the cross-linked network structure can be regulated by using the liquid crystal primitives contained in the liquid crystal epoxy resin monomer (LCE), thereby improving the thermal conductivity of the resin itself, that is, obtaining the so-called intrinsic thermal conductive insulating liquid crystal epoxy resin (LCER). The document (Composites Part B: Engineering, 2020, 185: 107784) discloses a method for synthesizing biphenyl liquid crystal elements LCE using 4,4'-dihydroxybiphenyl, triethylene glycol and epichlorohydrin as raw materials, using 4,4'-diaminodiphenylmethane (DDM) as a curing agent and boron nitride (BN) as a filler, and a casting method is used to prepare an intrinsically thermally conductive insulating liquid crystal epoxy resin with liquid crystal properties between 135 and 165°C, and its intrinsic thermal conductivity reaches 0.51W / (mK); compared with the thermal conductivity of ordinary epoxy resin of 0.20W / (mK), the thermal conductivity of the above-mentioned intrinsically thermally conductive insulating liquid crystal epoxy resin is significantly improved.

[0006] Organic silicon materials are another important synthetic material used as the matrix of thermal interface materials besides epoxy resins. Compared with the research and development of intrinsic thermal conductive polymer materials such as epoxy resins, there are few reports on the research and development of organic silicon polymers with intrinsic thermal conductivity in the literature, resulting in the research and development of silicon-based thermal interface materials mainly focusing on: (1) how to develop high thermal conductivity and high stability thermal conductive fillers; (2) how to reduce the particle size of fillers; (3) how to achieve the combination of fillers of different particle sizes and different types; (4) how to improve the surface and interface properties of fillers, improve the uniform dispersion of fillers in the silicon-based polymer matrix and increase the filler loading.

[0007] Although these aspects all affect the thermal conductivity of silicon-based thermal interface materials to varying degrees, there are few reports in the literature on how to improve the thermal conductivity of silicone polymers themselves and research and develop so-called intrinsic thermal conductive silicon-based polymer materials with high thermal conductivity. Summary of the invention

[0008] The present invention aims at the problem of insufficient thermal conductivity of organic silicon polymer materials and provides a polysiloxane material with high thermal conductivity. An inert polysiloxane fluid is modified by an organic metal compound of cerium to form Si-O-Ce bonds to improve the thermal conductivity of the polysiloxane fluid itself.

[0009] To achieve the above object, the technical solution adopted by the present invention is:

[0010] A method for preparing a cerium-modified polysiloxane fluid with high thermal conductivity comprises the steps of: reacting a cerium organic metal compound and polysiloxane in a closed inert gas environment, filtering the product, and removing low-boiling substances by reduced pressure distillation to obtain a cerium-modified polysiloxane material.

[0011] The cerium-modified polysiloxane fluid contains Si-O-Ce bonds in its molecules, has a number average molecular weight of 500-20000 g / mol, a polydispersity index of 1.05-3.00, a viscosity of 10-10000 mPa.s at 25° C., and a thermal conductivity of 0.180-0.250 W / (mK).

[0012] The cerium organometallic compound includes at least one of cerium acetate (CAS RN: 206996-60-3), cerium carbonate (CAS RN: 54451-25-1), cerium octanoate (CAS RN: 7435-02-1), cerium isooctanoate (CAS RN: 56797-01-4), cerium oxalate (CAS RN: 15750-47-7), cerium cyclohexane salt (CAS RN: 68514-63-6), cerous sulfate (CAS RN: 10450-59-6), cerium stearate (CAS RN: 10119-53-6), and cerium citrate (CAS RN: 512-24-3).

[0013] Preferably, the cerium organometallic compound is at least one of cerium stearate, cerium octoate, cerium isooctanoate, cerium oxalate, and cerium cyclohexane salt;

[0014] More preferably, the cerium organometallic compound is cerium stearate.

[0015] The mass ratio of the cerium organometallic compound to the total mass of the cerium organometallic compound and the polysiloxane is 0.0005 to 0.10:1. Preferably, the mass ratio of the cerium organometallic compound to the total mass of the cerium organometallic compound and the polysiloxane is 0.005 to 0.075:1; further preferably, the mass ratio of the cerium organometallic compound to the total mass of the cerium organometallic compound and the polysiloxane is 0.01 to 0.05:1;

[0016] The structural formula of the polysiloxane fluid is shown in Formula I:

[0017]

[0018] Among them, Ra, Rb, Rc, Rd, Re, Rf are independently selected from methyl, ethyl, phenyl or butyl; R1, R2, R3, R4, R5, R6 are independently selected from methyl, ethyl, phenyl, trifluoropropyl; m is 0 to 200, n is 0 to 200, p is 0 to 200, and m, n, p are not 0 at the same time.

[0019] The number average molecular weight of the polysiloxane fluid is 500 to 20,000 g / mol, and the viscosity at 25° C. is 10 to 10,000 mPa.s.

[0020] The inert gas includes at least one of nitrogen, argon and helium; preferably, the inert gas is selected from nitrogen, and its dew point is ≤-65°C;

[0021] The reaction pressure is 0.05 to 10 MPa, preferably 0.1 to 1.0 MPa; in some embodiments, the reaction pressure is 0.4 to 1.0 MPa;

[0022] The reaction temperature is 150-550°C, and the reaction time is 1-24h. Preferably, the reaction temperature is 250-450°C, and the reaction time is 5-15h; more preferably, the reaction temperature is 270-400°C, and the reaction time is 8-14h; in some embodiments, the reaction temperature is 250-350°C.

[0023] When the temperature is lower than 150°C, the thermal conductivity of the polysiloxane fluid cannot be improved because Si-O-Ce bonds cannot be generated between the cerium organometallic compound and the polysiloxane fluid; when the temperature is higher than 550°C, on the one hand, the polysiloxane fluid will degrade at high temperature, resulting in a decrease in the viscosity of the silicone oil and the conversion into a small molecule substance; on the other hand, the cerium organometallic compound will also oxidize and deteriorate at high temperature, and a cerium-modified polysiloxane fluid cannot be obtained.

[0024] The pressure of the reduced pressure distillation is -0.099 to -0.065 MPa, and the distillation temperature is 70 to 250° C.; preferably, the pressure of the reduced pressure distillation is -0.099 to -0.085 MPa, and the distillation temperature is 80 to 150° C. In some embodiments, the distillation temperature is 80 to 110° C.

[0025] The present invention also provides a cerium-modified polysiloxane fluid with high thermal conductivity prepared according to the preparation method. The cerium-modified polysiloxane fluid has a number average molecular weight of 500 to 20,000 g / mol, a polydispersity index of 1.05 to 3.00, a viscosity of 10 to 10,000 mPa.s at 25° C., and a thermal conductivity of 0.180 to 0.250 W / (mK).

[0026] The technical solution of the cerium-modified polysiloxane fluid disclosed in the present invention can not only improve the thermal conductivity of the polysiloxane fluid, but also the prepared cerium-modified polysiloxane fluid can be applied to various thermal interface materials, significantly improving the thermal conductivity of the thermal interface materials.

[0027] The thermal interface material is composed of polysiloxane, a filler surface treatment agent and a filler. Under the condition that the filler surface treatment agent, the filler dosage and the filler composition are the same, the cerium-modified polysiloxane fluid disclosed in the present invention is used to replace the conventionally used polysiloxane fluid to prepare the thermal interface material, and the thermal conductivity, thermal resistance, cone penetration and other information of the thermal interface material are measured and compared, which can show the significant effect of the cerium-modified polysiloxane fluid disclosed in the present invention on the thermal conductivity of the thermal interface material.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] (1) In the present invention, a cerium organometallic compound and a polysiloxane fluid are subjected to a closed reaction at high temperature to insert the cerium element into the polysiloxane molecular chain to form a Si-O-Ce bond, thereby improving the thermal conductivity of the polysiloxane fluid itself. By introducing the metal element cerium into the polysiloxane molecule and utilizing the characteristic that the metal element has a higher thermal conductivity than the Si element, a cerium-modified polysiloxane fluid having a higher thermal conductivity than polysiloxane is prepared;

[0030] (2) The cerium-modified polysiloxane fluid of the present invention has a simple preparation process and is easy to industrialize;

[0031] (3) The present invention uses the prepared cerium-modified polysiloxane fluid instead of the unmodified polysiloxane fluid as the matrix of the silicon-based thermal interface material, and adopts the preparation method of the flexible thermal interface material known in the art to obtain a flexible silicon-based thermal interface material with a higher thermal conductivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 The cerium-modified polydimethylsiloxane fluid prepared in Example 1 29 Si NMR spectrum.

[0033] Figure 2 FT-IR spectra of unmodified dual-terminal trimethylsilyl terminated polydimethylsiloxane (A) and cerium-modified polydimethylsiloxane fluid prepared in Example 4 (B). DETAILED DESCRIPTION

[0034] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiment. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. Those skilled in the art can make modifications or equivalent substitutions based on the understanding of the technical scheme of the present invention without departing from the spirit and scope of the technical scheme of the present invention, and all should be included in the protection scope of the present invention.

[0035] The raw materials used in the following specific embodiments are all purchased from the market. The chemical structural formula of the polysiloxane fluid used in the specific embodiments is:

[0036]

[0037] Among them, Ra, Rb, Rc, Rd, Re, Rf and R1, R2, R3, R4, R5, and R6 are all methyl groups, with a viscosity of 100 mPa.s at 25° C. and a number average molecular weight of 6000 g / mol.

[0038] 29 Si NMR test: The sample was dissolved in deuterated chloroform (CDCl3) solvent without internal standard and tested using a 500 MHz German Bruker NMR spectrometer (AVANCEⅢ);

[0039] FT-IR spectrum: The KBr tablet method is used to make the sample into a sample for FT-IR spectrum testing, and the wave number range is 4000~400cm -1 , resolution 4cm -1 ;

[0040] GPC test: PL-GPC50 gel permeation chromatograph was used, with polydimethylsiloxane (U.S. Polymer Standards Company) of known molecular weight as the standard sample, toluene as the mobile phase, flow rate of 1.0 mL / min, column temperature of 35°C, and molecular weight was calculated based on the time it took for the sample to flow out of the chromatographic column relative to the time it took for the standard sample to flow through.

[0041] Dynamic viscosity test: According to GB / T2794-2013 standard, the American Bookfeild DV2TRVTJ0 rotary viscometer is used for measurement at a constant temperature of 25±0.1℃ and a rotation speed of 200rpm. The test time is 5min, and the uncertainty of dynamic viscosity is 1%;

[0042] The thermal conductivity of liquids was determined according to ASTM D5334-2008, using the KDRX-Ⅱ transient rapid hot wire method thermal conductivity tester produced by Xiangtan Xiangyi Instrument Co., Ltd. The hot wire length was 30 mm, the hot wire resistance was 5 Ω, the test environment temperature was 25 °C, the test temperature continuous stabilization time was 30 s, and the temperature rise coordinate was 20 K.

[0043] Thermal conductivity test of silicone paste: According to ASTM D5470 method, the thermal conductivity and thermal resistance of the prepared composite material were tested using the DRL-Ⅲ thermal conductivity tester produced by Xiangtan Xiangyi Instrument Co., Ltd. The cold surface temperature was kept constant at 20°C, the heating plate temperature was set at 80°C, and the sample thickness was 2-3mm;

[0044] Cone penetration test: According to GB / T 269-2023 "Determination of cone penetration of greases and petroleum greases", the WM-221A of Guangdong Wanmu Instrument Co., Ltd. is used to test the cone penetration value of a 1 / 4 cone falling for 5 seconds in an environment of 25°C.

[0045] Example 1 Preparation of modified polysiloxane fluid with 1.0 wt% cerium salt content

[0046] S1: Add 0.50g (0.0017mol) of cerium stearate and 49.50g of a polydimethylsiloxane fluid with a viscosity of 100mPa.s at 25°C (i.e., in Formula I, Ra, Rb, Rc, Rd, Re, Rf and R1, R2, R3, R4, R5, R6 are all methyl groups) to a clean and dry reactor with a volume of about 500mL. Then, fill the reactor with dry nitrogen, exhaust the air, and replace it with nitrogen repeatedly 2 to 3 times, then fill the reactor with nitrogen to make the pressure in the reactor reach 0.5MPa (gauge pressure). Turn on stirring, control the speed to 400r / min, raise the temperature to 300°C, and maintain it at this temperature and pressure for 12h.

[0047] S2: After the reaction mixture is cooled to room temperature, the reaction mixture is transferred to a vacuum filtration device, and solid residues in the mixture are removed by filtration to obtain a clear filtrate.

[0048] S3: The clarified liquid obtained in S2 is transferred to a vacuum degassing device, and the low-boiling substances are removed by reduced pressure distillation at 100° C. and a vacuum degree of -100 kPa for 2 h to obtain a light yellow, clear and transparent cerium-modified polydimethylsiloxane fluid after removing small molecules.

[0049] Test: The product was subjected to GPC analysis, and the number average molecular weight of the cerium-modified polydimethylsiloxane fluid was 9100 g / mol, and the polydispersity index (PDI) was 1.75; the viscosity of the polymer at 25°C was 54.50 mPa·s as measured by a rotational viscosity instrument, and the thermal conductivity of the polymer was 0.182 W·m as measured by a transient rapid hot wire method thermal conductivity tester. -1 ·k -1 The cerium-modified polydimethylsiloxane fluid was 29 Si NMR analysis, the results are as follows Figure 1 As shown. Figure 1 It can be seen that the position of δ = 7.21 ppm is the terminal Si atom [(CH3)3 Si O-) chemical shift; δ = -21.97ppm is the dimethylsilyl oxygen chain [-(CH3)2 SiO-], the characteristic peak at this location is split into multiple peaks due to the introduction of cerium. In addition, δ = -8.35ppm is Ce-O- Si The characteristic chemical shift of cerium indicates that the cerium element is effectively incorporated into the polysiloxane molecular chain.

[0050] Example 2 Preparation of modified polydimethylsiloxane with 2.0 wt% cerium salt content

[0051] S1: This step is different from Example 1 in that 1.00 g (0.0018 mol) of cerium isooctanoate is used as the modified organic metal, and the amount of polydimethylsiloxane with a viscosity of 100 mPa.s at 25° C. is 49.00 g; the reaction temperature is 325° C.;

[0052] S2 and S3 are the same as in Example 1;

[0053] Test: The product was subjected to GPC analysis, and the number average molecular weight of the polymer was 7800 g / mol, and the polydispersity index (PDI) was 1.55; the viscosity of the polymer at 25°C was 65.50 mPa·s as measured by a rotational viscosity instrument, and the thermal conductivity of the polymer was 0.182 W·m as measured by a transient rapid hot wire method thermal conductivity tester. -1 ·k -1 .

[0054] Example 3 Preparation of modified polysiloxane fluid with 1.5 wt% cerium salt content

[0055] S1: This step is different from Example 1 in that the amount of cerium stearate used is 0.75 g, and the amount of polydimethylsiloxane with a viscosity of 100 mPa.s at 25°C is 49.25 g;

[0056] S2: This step is the same as in Example 1;

[0057] S3: This step is the same as in Example 1;

[0058] Test: The product was subjected to GPC analysis, and the number average molecular weight of the polymer was 8900 g / mol, and the polydispersity index (PDI) was 1.80; the viscosity of the polymer at 25°C was 72.50 mPa·s as measured by a rotational viscosity instrument, and the thermal conductivity of the polymer was 0.191 W·m as measured by a transient rapid hot wire method thermal conductivity tester. -1 ·k -1 .

[0059] Example 4 Preparation of modified polysiloxane fluid with 2.0 wt% cerium salt content

[0060] S1: This step is different from Example 1 in that the amount of cerium stearate used is 1.00 g, and the amount of polydimethylsiloxane with a viscosity of 100 mPa.s at 25°C is 49.00 g;

[0061] S2: This step is the same as in Example 1;

[0062] S3: This step is the same as in Example 1;

[0063] Test: The product was subjected to GPC analysis, and the number average molecular weight of the polymer was 8800 g / mol, and the polydispersity index (PDI) was 1.74; the viscosity of the polymer at 25°C was 94.50 mPa·s as measured by a rotational viscosity instrument, and the thermal conductivity of the polymer was 0.203 W·m as measured by a transient rapid hot wire method thermal conductivity tester. -1 ·k -1 .

[0064] The unmodified double-terminal trimethylsiloxy-terminated polydimethylsiloxane and the cerium-modified polydimethylsiloxane prepared in Example 4 were subjected to FT-IR tests. The results are as follows: Figure 2 As shown. Figure 2 It can be seen that the FT-IR spectrum of unmodified double-terminal trimethylsilyloxy-terminated polydimethylsiloxane ( Figure 2 A) Medium, 2962cm -1 、1409cm -1 The characteristic absorption peak of CH is at 1257cm -1 The left and right sides are the bending vibration absorption peaks of Si-(CH3)3; 1078cm -1 and 1012cm -1 It is the characteristic peak of Si-O-Si. Because the viscosity of the polydimethylsiloxane used is 100mPa.s, it has a certain degree of polymerization, so the Si-O-Si spectrum peak becomes broad and double peaks; 784cm -1 is the stretching vibration absorption peak of Si-CH3; Figure 2 The FT-IR spectrum of the cerium-modified double-terminal trimethylsilyloxy-terminated polydimethylsiloxane ( Figure 2 B) It can be seen that in the near-infrared region, Figure 2 The spectrum of B is different from Figure 2 The spectrum of A is at 605cm -1 With 553cm -1 Two new absorption peaks appear at the bottom, which are the characteristic absorption peaks of Ce-O (Rubber Industry, 2018, 65(11): 1248-1252), indicating that cerium and polysiloxane are combined through chemical bonds.

[0065] Example 5 Preparation of modified polysiloxane fluid with 2.5 wt% cerium salt content

[0066] S1: This step is different from Example 1 in that the amount of cerium stearate used is 1.25 g, and the amount of polydimethylsilane with a viscosity of 100 mPa.s at 25°C is 48.75 g;

[0067] S2: This step is the same as in Example 1;

[0068] S3: This step is the same as in Example 1;

[0069] Test: The product was subjected to GPC analysis, and the number average molecular weight of the polymer was 11300 g / mol, and the polydispersity index (PDI) was 1.78; the viscosity of the polymer at 25°C was 91.25 mPa·s as measured by a rotational viscosity instrument, and the thermal conductivity of the polymer was 0.190 W·m as measured by a transient rapid hot wire method thermal conductivity tester. -1 ·k -1 .

[0070] Example 6 Preparation of modified polysiloxane fluid with 3.0 wt% cerium salt content

[0071] S1: This step is different from Example 1 in that the amount of cerium stearate used is 1.5 g, and the amount of polydimethylsilane with a viscosity of 100 mPa.s at 25°C is 48.50 g;

[0072] S2: This step is the same as in Example 1;

[0073] S3: This step is the same as in Example 1;

[0074] Test: The product was subjected to GPC analysis, and the number average molecular weight of the polymer was 8900 g / mol, and the polydispersity index (PDI) was 1.83; the viscosity of the polymer at 25°C was 66.5 mPa·s as measured by a rotational viscosity instrument, and the thermal conductivity of the polymer was 0.181 W·m as measured by a transient rapid hot wire method thermal conductivity tester. -1 ·k -1 .

[0075] Example 7 Preparation of a modified polysiloxane fluid containing 2.0 wt% cerium salt at 250°C

[0076] S1: Add 1.00g (0.0024mol) of cerium stearate and 49.00g of a double-terminal trimethylsiloxy-terminated polydimethylsiloxane fluid with a viscosity of 100mPa.s at 25°C to a clean and dry reactor with a volume of about 500mL, then fill nitrogen into the reactor, exhaust the air, replace it with nitrogen 2 to 3 times, and then fill nitrogen into the reactor to make the pressure in the reactor reach 0.4MPa (gauge pressure). Start stirring, control the speed to 400r / min, raise the temperature to 250°C, and maintain it at this temperature and pressure for 12h.

[0077] S2: This step is the same as in Example 1;

[0078] S3: This step is the same as in Example 1;

[0079] Test: The product was subjected to GPC analysis, and the number average molecular weight of the polymer was 9500 g / mol, and the polydispersity index (PDI) was 1.70; the viscosity of the polymer at 25°C was 91.50 mPa·s as measured by a rotational viscosity instrument, and the thermal conductivity of the polymer was 0.180 W·m as measured by a transient rapid hot wire method thermal conductivity tester. -1 ·k -1 .

[0080] Example 8 Preparation of a modified polysiloxane fluid containing 2.0 wt% cerium salt at 275°C

[0081] S1: Add 1.00g (0.0024mol) of cerium stearate and 49.00g of a polydimethylsiloxane fluid with a viscosity of 100mPa.s at 25°C and double-end trimethylsiloxy terminated into a clean and dry reactor with a volume of about 500mL, then fill nitrogen into the reactor, exhaust the air, replace it with nitrogen 2 to 3 times, and then fill nitrogen into the reactor to make the pressure in the reactor reach 0.4MPa (gauge pressure). Start stirring, control the speed to 400r / min, heat to 275°C, and maintain it at this temperature and pressure for 12h.

[0082] S2: This step is the same as in Example 1;

[0083] S3: This step is the same as in Example 1;

[0084] Test: The product was subjected to GPC analysis, and the number average molecular weight of the polymer was 9700 g / mol, and the polydispersity index (PDI) was 1.75; the viscosity of the polymer at 25°C was 80.51 mPa·s as measured by a rotational viscosity instrument, and the thermal conductivity of the polymer was 0.187 W·m as measured by a transient rapid hot wire method thermal conductivity tester. -1 ·k -1 .

[0085] Example 9 Preparation of a modified polysiloxane fluid containing 2.0 wt% cerium salt at 325°C

[0086] S1: Add 1.00g (0.0024mol) of cerium stearate and 49.00g of a double-terminal trimethylsiloxy-terminated polydimethylsiloxane fluid with a viscosity of 100mPa.s at 25°C to a clean and dry reactor with a volume of about 500mL, then fill nitrogen into the reactor, exhaust the air, and replace it with nitrogen 2 to 3 times, then fill nitrogen into the reactor to make the pressure in the reactor reach 0.4MPa (gauge pressure). Start stirring, control the speed to 400r / min, raise the temperature to 325°C, and maintain it at this temperature and pressure for 12h.

[0087] S2: This step is the same as in Example 1;

[0088] S3: This step is the same as in Example 1;

[0089] Test: The product was subjected to GPC analysis, and the number average molecular weight of the polymer was 9700 g / mol, and the polydispersity index (PDI) was 1.75; the viscosity of the polymer at 25°C was 79.25 mPa·s as measured by a rotational viscosity instrument, and the thermal conductivity of the polymer was 0.196 W·m as measured by a transient rapid hot wire method thermal conductivity tester. -1 ·k -1 .

[0090] Example 10 Preparation of a modified polysiloxane fluid containing 2.0 wt% cerium salt at 350°C

[0091] S1: Add 1.00g (0.0024mol) of cerium stearate and 49.00g of a polydimethylsiloxane fluid with a viscosity of 100mPa.s at 25°C and double-end trimethylsiloxy terminated, into a clean and dry reactor with a volume of about 500mL, then fill nitrogen into the reactor, exhaust the air, replace it with nitrogen 2 to 3 times, and then fill nitrogen into the reactor to make the pressure in the reactor reach 0.4MPa (gauge pressure). Start stirring, control the speed to 400r / min, heat to 350°C, and maintain at this temperature and pressure for 12h.

[0092] S2: This step is the same as in Example 1;

[0093] S3: This step is the same as in Example 1;

[0094] Test: The product was subjected to GPC analysis, and the number average molecular weight of the polymer was 9900 g / mol, and the polydispersity index (PDI) was 1.81; the viscosity of the polymer at 25°C was 58.50 mPa·s as measured by a rotational viscosity instrument, and the thermal conductivity of the polymer was 0.191 W·m as measured by a transient rapid hot wire method thermal conductivity tester. -1 ·k -1 .

[0095] Comparative Example 1 Preparation of modified silicone oil containing organic metal compounds without adding cerium at 300°C

[0096] S1: Add 50.00g of a double-terminal trimethylsiloxy-terminated polydimethylsiloxane fluid with a dynamic viscosity of 100mPa.s at 25°C to a clean and dry reactor with a volume of about 500mL, then fill the reactor with nitrogen, exhaust the air, and replace it with nitrogen 2 to 3 times, and then fill the reactor with nitrogen to make the pressure in the reactor reach 0.45MPa (gauge pressure). Start stirring, control the speed to 400r / min, raise the temperature to 300°C, and maintain it at this temperature and pressure for 12h.

[0097] S2: After cooling to room temperature, the clarified liquid obtained in S1 is transferred to a vacuum degassing device, and low-boiling-point substances are removed by reduced pressure distillation at 100°C and vacuum degree -100 kPa for 2 h to obtain a high-temperature treated polydimethylsiloxane fluid after removing small molecules.

[0098] Test: The product was subjected to GPC analysis, and the number average molecular weight of the polymer was 9700 g / mol, and the polydispersity index (PDI) was 1.72; the viscosity of the polymer at 25°C was 95.50 mPa·s as measured by a rotational viscosity instrument, and the thermal conductivity of the polymer was 0.179 W·m as measured by a transient rapid hot wire method thermal conductivity tester. -1 ·k -1 .

[0099] Comparative Example 2: Preparation of thermal conductive silicone paste using untreated polydimethylsiloxane fluid

[0100] The number average molecular weight of the untreated double-terminal trimethylsiloxy-terminated polydimethylsiloxane fluid with a dynamic viscosity of 100 mPa.s at 25°C was 8700 g / mol, the PDI was 1.86, and the thermal conductivity was 0.179 W·m -1 ·k -1 .

[0101] Application Examples

[0102] In order to demonstrate the improvement effect of the cerium-modified polysiloxane fluid disclosed in the present invention on the thermal conductivity of the thermal interface material, the present invention also uses the cerium-modified polysiloxane fluid as the continuous phase, alumina filler as the dispersed phase, and an inorganic filler surface modifier to prepare a thermally conductive silicone paste, and compares the thermal conductivity of the thermally conductive silicone paste prepared by not using the technical scheme of the present application, using other polysiloxane fluids as the continuous phase, alumina filler with the same composition and amount as the dispersed phase, and adding an inorganic filler surface modifier with the same structure and amount.

[0103] The modified polydimethylsiloxane fluids prepared in the embodiments and comparative examples are used to prepare a thermally conductive silicone paste: 10 parts by weight of the modified polydimethylsiloxane fluids in the above-mentioned different embodiments and comparative examples are respectively mixed with 1 part by weight of α-trimethylsiloxy-ω-triethoxysilylethyl-terminated polydimethylsiloxane with a degree of polymerization n=12 prepared according to the literature (European Polymer Journal, 2024, 211, 113042) (hereinafter referred to as inorganic filler surface modifier), and then 279.3 parts by weight of dried and ground alumina fillers with an average particle size of 70um, 167.6 parts by weight of an average particle size of 3um and 74.5 parts by weight of 0.5um are added to the above liquid mixture at one time or in batches, and are evenly dispersed in a high-speed shear dispersion equipment and degassed to obtain a thermally conductive silicone paste with a mixed particle size alumina volume fraction of 86%.

[0104] In each embodiment and comparative example, the thermal conductivity parameters and cone penetration data of the polysiloxane fluid and the prepared silicone paste are shown in Table 1. Except for Example 2 which uses cerium isooctanoate, the other embodiments use cerium stearate.

[0105] It can be seen from the test data in Table 1 that the cerium-modified polysiloxane fluid prepared by the present application has good thermal conductivity. In Comparative Example 1, no organic metal salt of cerium was added, and only the silicone oil was subjected to high temperature treatment. The thermal conductivity of the silicone oil did not change compared with the silicone oil that was not subjected to high temperature treatment (Comparative Example 2); the thermal conductivity of the thermal conductive silicone paste prepared using the silicone oil subjected to high temperature treatment in Comparative Example 1 increased, and the cone penetration of the silicone paste increased. The thermal conductivity of the cerium-modified silicone oil prepared using the technical solution of the present application was improved compared with that of Comparative Examples 1 and 2, and the thermal conductivity of the thermal conductive silicone paste prepared using these cerium-modified silicone oils was also improved.

[0106] Compared with Comparative Example 2, the thermal conductivity of the cerium-modified polysiloxane fluids prepared in Examples 1 to 10 of the present application is increased by 0.6% to 13.4%; using these cerium-modified polysiloxane fluids as a matrix and adding alumina particles of large, medium and small particle sizes to make a silicone paste, the silicone paste prepared in Example 4 has the best thermal conductivity, reaching 6.84W / (mK), and its 1 / 4 cone penetration reaches 62.0mm. Therefore, the amount of mixed particle size alumina filler can be further increased to prepare a thermally conductive silicone paste with a cone penetration that meets application requirements and a higher thermal conductivity.

[0107] From the cone penetration measurement data in Table 1, it can be seen that the main factors affecting the cone penetration of silicone paste are the type of inorganic filler surface modifier and the filling ratio of alumina filler. The cone penetration has a certain influence on the interface thermal resistance during the use of thermal conductive materials. When the cone penetration is high, the fluidity of silicone paste is good, the thermal interface material and the contact interface have better adhesion, and the thermal resistance during heat transfer is reduced.

[0108] By comparing Example 1 with Examples 4 to 6, it can be seen that at the same processing temperature (300°C), different masses of cerium salts (cerium stearate) affect the thermal conductivity of silicone oil and the thermal conductivity of silicone paste prepared using the same formula, that is, with the increase of the amount of cerium salt, the thermal conductivity of the cerium-modified silicone oil and the silicone paste prepared with it as a component shows a trend of gradually increasing; but when the amount of cerium salt exceeds 2.0wt%, the thermal conductivity of the cerium-modified silicone oil and the silicone paste prepared with it as a component shows a trend of gradually decreasing, indicating that there is an optimal range for the amount of cerium salt.

[0109] Comparing Example 4 with Examples 7 to 10, it can be seen that when the amount of cerium stearate is the same (2wt%), the effect of the treatment temperature on the thermal conductivity of the cerium-modified silicone oil and the thermal conductivity of the silicone paste prepared using the same formula, that is, as the treatment temperature gradually increases from 250°C to 300°C, the thermal conductivity of the cerium-modified silicone oil gradually increases from 0.180W / (mK) to 0.203W / (mK), the thermal conductivity of the silicone paste prepared using these silicone oils gradually increases from 6.32W / (mK) to 6.84W / (mK), and the thermal resistance increases from 7.66K·cm 2 / W is reduced to 3.94K·cm 2 / W, 0.1mm cone penetration increased from 54.1mm to 62.0mm; when the treatment temperature continued to increase from 300℃ to 350℃, the thermal conductivity of the cerium-modified silicone oil showed a downward trend, from 0.203W / (mK) to 0.191W / (mK), and the thermal conductivity of the silicone paste prepared from these silicone oils also showed an overall downward trend, indicating that there is a suitable range of treatment temperature. When the temperature exceeds this range, the thermal conductivity of the prepared cerium-modified silicone oil cannot reach the optimal value.

[0110] Table 1 Performance test results of modified polysiloxane fluid and thermal conductive silicone paste prepared in each embodiment and comparative example

[0111]

[0112] The above describes the basic principles, main features and advantages of the present application. Those skilled in the art should understand that the present application is not limited by the above embodiments, and the above embodiments and the specification only describe the principles of the present application. The present application may have various changes and improvements without departing from the spirit and scope of the present application, and these changes and improvements fall within the scope of the present application for which protection is sought. The scope of protection claimed by the present application is defined by the attached claims and their equivalents.

Claims

1. A method for preparing a cerium-modified polysiloxane fluid with high thermal conductivity, characterized in that: Includes steps: The cerium organic metal compound and the polysiloxane fluid are reacted in a closed inert gas environment, and the product is filtered and distilled under reduced pressure to remove low-boiling substances to obtain a cerium-modified polysiloxane material.

2. The method for preparing the cerium-modified polysiloxane fluid with high thermal conductivity according to claim 1, characterized in that: The cerium organometallic compound includes at least one of cerium acetate, cerium carbonate, cerium octoate, cerium isooctanoate, cerium oxalate, cerium naphthenate salt, cerous sulfate, cerium stearate, and cerium citrate.

3. The method for preparing the cerium-modified polysiloxane fluid with high thermal conductivity according to claim 1, characterized in that: The cerium-modified polysiloxane fluid has a number average molecular weight of 500 to 20,000 g / mol, a polydispersity index of 1.05 to 3.00, a viscosity of 10 to 10,000 mPa.s at 25° C., and a thermal conductivity of 0.180 to 0.250 W / (mK).

4. The method for preparing the cerium-modified polysiloxane fluid with high thermal conductivity according to claim 1, characterized in that: The mass ratio of the cerium organometallic compound to the total mass of the cerium organometallic compound and polysiloxane is 0.0005 to 0.10:

1.

5. The method for preparing the cerium-modified polysiloxane fluid with high thermal conductivity according to claim 1, characterized in that: The structural formula of the polysiloxane fluid is shown in Formula I: Among them, Ra, Rb, Rc, Rd, Re, Rf are independently selected from methyl, ethyl, phenyl or butyl; R1, R2, R3, R4, R5, R6 are independently selected from methyl, ethyl, phenyl, trifluoropropyl; m is 0 to 200, n is 0 to 200, p is 0 to 200, and m, n, p are not 0 at the same time.

6. The method for preparing the cerium-modified polysiloxane fluid with high thermal conductivity according to claim 1, characterized in that: The number average molecular weight of the polysiloxane fluid is 500 to 20,000 g / mol, and the viscosity at 25° C. is 10 to 10,000 mPa.s.

7. The method for preparing a cerium-modified polysiloxane fluid with high thermal conductivity according to claim 1, characterized in that: The inert gas includes at least one of nitrogen, argon and helium; the reaction pressure is 0.05-10 MPa.

8. The method for preparing the cerium-modified polysiloxane fluid with high thermal conductivity according to claim 1, characterized in that: The reaction temperature is 150-550° C., and the reaction time is 1-24 hours.

9. The method for preparing the cerium-modified polysiloxane fluid with high thermal conductivity according to claim 1, characterized in that: The pressure during the reduced pressure distillation is -0.099 to -0.065 MPa, and the distillation temperature is 70 to 250°C.

10. The cerium-modified polysiloxane fluid with high thermal conductivity obtained by the preparation method according to any one of claims 1 to 9, characterized in that: The cerium-modified polysiloxane fluid has a number average molecular weight of 500 to 20,000 g / mol, a polydispersity index of 1.05 to 3.00, a viscosity of 10 to 10,000 mPa.s at 25° C., and a thermal conductivity of 0.180 to 0.250 W / (mK).